Developing deeper understanding of green inhibitors for corrosion of reinforcing steel in concrete - Ismail, Mohamed; Raja, P.; Salawu, A. (2015)
© 2015, IGI Global. All rights reserved. Corrosion of reinforcing steel in concrete is a very serious and significant problem in the construction industry. The primary cause of corrosion of reinforcing steel is chloride attack or carbonation. Among several protection measures for concrete corrosion, the usage of corrosion inhibitors is very attractive from the view of cost and ease of application. Though there are numerous organic and inorganic compounds that have been tested and applied industrially as corrosion inhibitors, restrictive environmental regulations have compelled and motivated researchers towards the development of cheap, non-toxic and environmentally benign natural or green corrosion inhibitors. Recent studies on green inhibitors have shown that they are more effective and highly environmentally benign compared to synthetic inhibitors used in the industries. This chapter contributes to developing awareness, understanding and innovative involvement of materials and engineering students in this area that is vital to reduce expenditure related to corrosion problems when they serve in the industries.